Regulatory circuits mediated by lectin-glycan interactions in autoimmunity and cancer - Rabinovich, Gabriel Adrián (2012)
Numerous regulatory programs have been identified that contribute to the restoration of homeostasis at the conclusion of immune responses and to safeguarding against the detrimental effects of chronic inflammation and autoimmune pathology. Malignant cells may usurp these pathways to create immunosuppressive networks that thwart antitumor responses. Herein we review the role of endogenous lectins (C-type lectins, siglecs, and galectins) and specific N- and O-glycans generated by the coordinated action of glycosyltransferases and glycosidases that together promote regulatory signals that control immune cell homeostasis. We also discuss the mechanisms by which glycan-dependent regulatory programs integrate into canonical circuits that amplify or silence immune responses related to autoimmunity and neoplastic disease.